Determination of ultimate tensile properties in geogrids according ASTM regulation - Campos Zeledón, Jordan Josué (2020)
Recently the ASTM D6637 test method of the American Association of Materials Testing (ASTM) was implemented in the National Laboratory of Materials and Structural Models of the University of Costa Rica (LANAMME UCR). In the verification stage of the correct implementation of the test method, we worked with 2 types of geogrids samples used as reinforcement at the national level; which were tested to determine their tensile mechanical properties; ie (ultimate strength and ultimate deformation). Once these characteristics were obtained, we proceeded to compare them with the data reported in their technical specifications. In this stage, inconsistencies were found between the data found at the laboratory level and those reported by the manufacturer; which gave indications of possible overvaluations in the data reported by the manufacturers and marketers of geogrids. There is also evidence of data reports in values ​​different to the MARV specification, which is the one adopted by ASTM in the subject of quality control. This document is derived from the final work of graduation: "Implementation of the test methods for the determination of the properties at the same time in the geogrids and geotextiles according to the ASTM D6637 and ASTM D4595 standards" (see bibliographical reference 6).